2017
DOI: 10.1101/180943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of p53 improves CRISPR/Cas - mediated precision genome editing

Abstract: We report here that genome editing by CRISPR/Cas9 induces a p53-mediated DNA damage response and cell cycle arrest. Transient inhibition of p53 prevents this response, and increases the rate of homologous recombination more than five-fold. This provides a way to improve precision genome editing of normal cells, but warrants caution in using CRISPR for human therapies until the mechanism of the activation of p53 is elucidated.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 18 publications
1
21
1
Order By: Relevance
“…We also demonstrated that wild-type p53 does not appreciably restrict targeted knockin by tandem paired nicking. In contrast, when a Cas9-nuclease-based method was applied, targeted knockin preferentially occurred in p53-suppressed cells as described previously (Haapaniemi et al, 2018;Ihry et al, 2018). A concern raised here is that when using Cas9 nuclease, designed genetic modification might be preferentially introduced into cells with compromised p53 function, which can spontaneously emerge within cultured cells.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…We also demonstrated that wild-type p53 does not appreciably restrict targeted knockin by tandem paired nicking. In contrast, when a Cas9-nuclease-based method was applied, targeted knockin preferentially occurred in p53-suppressed cells as described previously (Haapaniemi et al, 2018;Ihry et al, 2018). A concern raised here is that when using Cas9 nuclease, designed genetic modification might be preferentially introduced into cells with compromised p53 function, which can spontaneously emerge within cultured cells.…”
Section: Discussionmentioning
confidence: 87%
“…p53 Does Not Significantly Affect Targeted Knockin by Tandem Paired Nicking It was recently shown that Cas9-nuclease-based genome editing triggers the activation of the p53 signaling pathway and G1 cell cycle arrest. As targeted knockin is mediated by HDR, which predominantly occurs in the S through G2 phases, Cas9 nuclease inherently obstructs targeted knockin in a p53-dependent manner (Haapaniemi et al, 2018;Ihry et al, 2018).…”
Section: Tandem Paired Nicking Does Not Trigger a Significant Level Omentioning
confidence: 99%
See 1 more Smart Citation
“…S4E), and P21 sgRNAs did not enrich in H1-hESCs. In contrast, in a genome-scale screen in retinal pigment epithelial cells, where Cas9 activity causes TP53-dependent cell cycle arrest rather than apoptosis, sgRNAs targeting TP53 and P21/CDKN1A were enriched while PMAIP1 sgRNAs were not (File S5) (Haapaniemi et al, 2017). Overall, these results indicate that PMAIP1 plays a role in the sensitivity of hPSCs to DNA damage and highlights the ability of genome-scale CRISPR screens to identify cell type-specific genes important for the fitness of pluripotent stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…programmable endonucleases that drive random or site-specific integration, respectively (Ivics et al, 2009;Mikuni et al, 2016;Suzuki et al, 2016). Transposases provide the highest efficiency of integration, a process that they directly mediate, whereas endonucleases only indirectly stimulate transgene insertion through the host repair machinery upon target locus cleavage, with potential detrimental side effects (Haapaniemi et al, 2018). Transposon-based systems achieve high rates of integration with >1-kb-long sequences, can handle cargos up to 100 kb (Jung et al, 2016;Li et al, 2011), and are thus ideal for demanding applications requiring integration of one or multiple large transgenes comprised of a promoter and gene of interest (GOI).…”
Section: Accessmentioning
confidence: 99%